Called to be Protagonists. Education Policy, Youth Mobilization and Participation of Secondary Education Students. Province of Buenos Aires, Argentina, 2009-2014 - Larrondo, Marina (Education Policy Analysis Archives, 2015)
In this work we seek to analyze the characteristics of the political participation of secondary students in their schools and in social movement organizations. Our empirical findings show that these characteristics were related to recent changes in provincial educational policy, its effects and multiple appropriations from the main characters (administrators, students and activists). We suggest that policy changes have complex and multidimensional relationships with the political organizations of youth activism. Moreover, we suggest that this confluence has revitalized student participation and the creation of student organizations, both independent and partisan. We consider that this work can enrich the reflections regarding the relationship between educational policies, schools and collective action. Last but not least, the Argentinian case is set in a regional context where the literature describes student political participation as being confrontational towards the State and other politically representative institutions. Finally, our case allows us to reflect on other possible relations between these spaces and political participation of the youth.